The Role of Teachers in the Development of Learning Media for Block Play in Early Childhood Cognitive Development - Itryah; Dea Pertiwi (Indonesian Journal of Behavioral Studies, 2024)
The role of a teacher is very important in providing enjoyable and interactive learning methods, one of which is block play, to achieve cognitive development in preschool-aged children. This research uses the library research method or literature study approach. In this research, references include books, previous research journals, articles in the form of magazines or newspapers, and other scientific writings. This research provides a description of the role of teachers in the development of learning methods such as block play in the cognitive development of preschool children. Semi-structured interviews and structured observations of teachers who teach preschool children. The contributions of the research include a) interactive learning activities that incorporate games during learning, b) active participation of teachers in implementing interactive learning methods can enhance cognitive development, c) the establishment of cooperation with early childhood education providers and kindergartens, d) creativity that can be created and developed to improve cognitive abilities. The role of teachers in the development of interactive learning methods through block play becomes the focus of discussion to enhance cognitive abilities, so that preschool children have good memory, problem-solving skills, intellectual capacity, logic, and decision-making, especially at the later stages of development when children enter elementary school.